Chest pain prevalence, causes, and disposition in the emergency department of a regional hospital in Pretoria - Mimi Geyser; Selma Smith (AOSIS, 2016)
Background: Chest pain is a common clinical syndrome. However, there is a paucity of African studies describing the causes, prevalence, aetiology, and disposition of patients with chest pain presenting in the emergency department (ED). Aim: The aim of this retrospective descriptive study was to determine the prevalence, causes, demographics, and disposition of all adult patients with the main complaint of chest pain presenting at the ED of a regional hospital in South Africa. Methods: Records of all patients 18 years and older presenting with the complaint of chest pain from 1 December 2011 through 10 April 2012 were assessed. A data collection sheet capturing patient demographics and disposition from the ED was used. The diagnosis was subdivided into groups: cardiovascular, respiratory, gastrointestinal, musculoskeletal, psychiatric/psychogenic, other, and unknown. Results: Of the 312 patients presenting with chest pain, 210 patient files were retrieved. The prevalence of non-traumatic chest pain was 1.66%. Respiratory disease was the most common cause (36.19%), with pneumonia the most common diagnosis (24.40%). Logistic regression showed diagnoses of acute cardiovascular disease or respiratory disease, older age, and transport by ambulance as being associated with admission. Conclusion: The main cause of acute chest pain was found to be respiratory disease, followed by musculoskeletal disorders. In the African context, the aetiology of acute chest pain differs from that in first world countries. Health workers should therefore pay special attention to respiratory conditions during diagnosis and management in African patients with acute chest pain. Keywords: acute chest pain; prevalence; causes; disposition; emergency department